SOCIAL MEDIA MARKETING AND ONLINE CUSTOMER ENGAGEMENT: THE MEDIATING ROLE OF ONLINE TRUST (CASE STUDY OF RENAN STORE IPHONE ONLINE RESELLER) - Irene Potabuga; Willem J. F. A. Tumbuan; Regina T. Saerang (Universitas Sam Ratulangi, 2022)
Today’s businesses are operating in an environment where customers are well-versed in social media and have easy access to technology. Social Media has changed the way businesses engage with their customers or potential customers. However, buying electronics online is prone to e-commerce fraud (not original, poor quality, etc.). This study aims to determine the effect of Social Media Marketing (X) on Online Customer Engagement (Z) with Online Trust (Y) as mediating variables in Renan Store (iPhone reseller) customers. This study uses 100 samples collected through an online questionnaire with a purposive sampling technique. The researcher conducted the path analysis method to analyze the effect of the independent variable on the dependent variable with the mediating variable. The results of this study indicate that Social Media Marketing positively and significantly affects Online Customer Engagement. This study also proves that Online Trust has a positive and significant relationship with Social Media Marketing. The results of this study have also shown that Online Trust can be used as a mediating variable for the effects of Social Media Marketing on Online Customer Engagement in Renan Store with an indirect effect of 0.323 which is greater than the direct effect of 0.285.